Analisis Kinerja Pemimpin Unit Kegiatan Mahasiswa Universitas Andalas Kampus Payakumbuh - Desri, Syuryatman; Mawadda, Firli; Zikra, Zeni Nur (Al-DYAS, 2023)
The Student Organization is a forum for university-level student members, where this organization will act as a catalyst for the growth of student aspirations. In addition, student organizations play an important role in developing student interests and talents. The purpose of this study is to find out how the performance of student activity unit leaders is. The method used in this research is a qualitative approach. Data collection used questionnaires to 5 respondents and data processing was processed using SPSS. The result is a graph from SPSS which states that each UKM leader has a variable with a good rating in providing the best performance for the UKM he leads. There are no UKM leaders who fulfill all the leader assessment variables.